2023
DOI: 10.3390/ijms24086950
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification and Analysis of Stress Response of Trehalose-6-Phosphate Synthase and Trehalose-6-Phosphate Phosphatase Genes in Quinoa

Abstract: Saline-alkali stress seriously affects the yield and quality of crops, threatening food security and ecological security. Improving saline-alkali land and increasing effective cultivated land are conducive to sustainable agricultural development. Trehalose, a nonreducing disaccharide, is closely related to plant growth and development and stress response. Trehalose 6-phosphate synthase (TPS) and trehalose-6-phosphate phosphatase (TPP) are key enzymes catalyzing trehalose biosynthesis. To elucidate the effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 84 publications
1
11
0
Order By: Relevance
“…Surprisingly, in this study, it was observed that sucrose and trehalose levels increased under saline-alkaline treatment alone, regardless of the altered expression of GmTPP genes and the decrease in glucose, fructose, and starch contents. Notably, high levels of soluble carbohydrate can positively regulated genes involved in sugar sensing and carbon metabolism under saline conditions [ 51 ]. For example, enhancing sucrose synthesis and reducing sucrose decomposition to increase sucrose content alleviated salt stress in salt-tolerant sweet sorghum [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, in this study, it was observed that sucrose and trehalose levels increased under saline-alkaline treatment alone, regardless of the altered expression of GmTPP genes and the decrease in glucose, fructose, and starch contents. Notably, high levels of soluble carbohydrate can positively regulated genes involved in sugar sensing and carbon metabolism under saline conditions [ 51 ]. For example, enhancing sucrose synthesis and reducing sucrose decomposition to increase sucrose content alleviated salt stress in salt-tolerant sweet sorghum [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…In wheat, salt stress was shown to induce eight TaTPPs and repress three others (Du et al, 2022). In quinoa (Chenopodium quinoa), CqTPP4 was shown to decrease significantly under saline-alkali stress (Wang et al, 2023b). In salt-stressed maize plants, TPP expression was differentially altered F I G U R E 7 Effects of cold, osmotic, salt, drought, oxidative and heat stresses on the expression of Arabidopsis TPP genes.…”
Section: Water Limitation and Salt Stressmentioning
confidence: 99%
“…In wheat, salt stress was shown to induce eight TaTPPs and repress three others (Du et al, 2022). In quinoa ( Chenopodium quinoa ), CqTPP4 was shown to decrease significantly under saline‐alkali stress (Wang et al, 2023b). In salt‐stressed maize plants, TPP expression was differentially altered in leaves, kernels and cobs, indicating that Tre6P signalling may have different roles in source and sink tissues (Henry et al, 2015).…”
Section: Role Of Trehalose 6‐phosphate Phosphatases In Plant Metaboli...mentioning
confidence: 99%
“…Afterward, T6P is dephosphorylated into trehalose through the action of trehalose-6-phosphate phosphatase (TPP) [ 13 ]. With the advancement of high-throughput DNA sequencing technology, researchers have successfully identified TPS and TPP gene family members in the genomes of all major plant taxa [ 4 , 14 , 15 ]. This significant finding suggests that trehalose metabolism, regulated by these genes, is widely distributed and prevalent throughout the plant kingdom [ 2 , 16 ].…”
Section: Introductionmentioning
confidence: 99%